Juridical Analysis of the Determination of Child Custody in Dual Citizenship Divorce Cases: A Case Study of Supreme Court Decision No. 2021 K/Pdt/2020 - Putri, Gusni Cahaya; Prastyanti, Rina Arum (Formosa Journal of Multidisciplinary Research, 2024)
The determination of child custody in divorce cases involving dual citizens is a complex issue that requires special attention to Indonesian legal jurisdiction. This study analyzes how Indonesian legal jurisdiction is applied in determining child custody in divorce cases involving couples of different nationalities, based on the Marriage Law No. 1 of 1974 and related international regulations. The case study of the Supreme Court Decision No. 2021 K/Pdt/2020 was also studied to understand the factors considered in decisions related to child custody. The main factors that the Supreme Court considers include the psychological and emotional well-being of the child, the financial ability of the parents, the relationship between the child and the parents, as well as the residence and nationality of the child. The results of the study show that custody decisions are always aimed at the best interests of the child, taking into account relevant national and international legal aspects.